Assessing the Age Determination Cases Which Have Been Analyzed at Forensic Medicine Departments of 5 Different Region's Universities in Turkey Between Years 1998-2005 - Isir, Aysun Baransel; Buken, Bora; Tokdemir, Mehmet; Dulger, H. Ergin; Erel, Ozlem; Fedakar, Rece (Ortadogu Ad Pres & Publ Co, 2009)
Objective: In forensic medicine practice, age determination is used for forensic identifications of living and dead people. Age determination is important to clarify the legal obligations of people and their punishment. Recently, the most common method for age prediction is physical examination, as well as radiologic evaluation of bone growth and other methods designed for age prediction. The aim of our research was to assess the age determination cases, which were analyzed according to the Gok Atlas frequently used in Turkey, in the Department of Forensic Medicine in 5 different universities, Gaziantep, Firat, Adnan Menderes, Uludag and Duzce. Material and Methods: In this study, 275 male and 312 female cases were included who were referred to the university by the courts for age determination between 1998 and 2005 years. Bone ages and chronological ages were compared radiologically to determine the similarities or differences in several age groups. Results: In the 0-12 age group (total 39 cases), 31 cases (79.5%) had bones ages higher than the chronological ages, 6 cases (15.4%) had equivalent bone and choronological ages and 2 cases (5.1%) had bone ages lower than the chronological ages. In the 13-22 age group, bone ages were higher than chronological ages in 79.8%, lower in but %9.6 and the were equivalent to chronological ages in 10.6%. Conclusion: Physical growth seems to affect the growth of bones in the pubertal period. For age determination after puberty, the use of more sophisticated methods is suggested In conclusion, a method of age determination suitable for the Turkish population is urgently required.
1998-2005 Yillari Arasinda Türkiye' de 5 Farkli Bölgedeki Üniversitelerin Adli Tip Anabilim Dallarinda Raporladirilan yaş tayini olgularinin i?rdelenmesi
Keywords: Age determination by skeleton; forensic medicine